Scale inhibitor used in ultrafiltration and reverse osmosis processes, and preparation method and application thereof

By using a combination of polyaspartic acid, polyepoxysuccinic acid, composite materials and stabilizers in ultrafiltration and reverse osmosis processes, a scale inhibitor with broad-spectrum scale inhibition performance was prepared, which solved the problems of complexity, high cost and difficulty in verifying the production process of existing scale inhibitors, and achieved efficient and economical water treatment effect.

CN119591262AActive Publication Date: 2025-03-11BEIJING WATER-RES ENVIRONMENT TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411886060.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-11
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing scale inhibitors have problems such as complex production process, high cost and difficulty in long-term validation in ultrafiltration and reverse osmosis processes, especially in ensuring long-term stability and broad-spectrum scale inhibition.

Method used

A combination of polyaspartic acid, polyepoxysuccinic acid, composite materials and stabilizers is used to prepare a scale inhibitor used in ultrafiltration and reverse osmosis processes through the joint action of multiple mechanisms such as chelation, dispersion, adsorption and thickening. The scale inhibitor includes 20-30 parts of polyaspartic acid, 5-9 parts of polyepoxysuccinic acid, 5-9 parts of composite glue, 1-3 parts of defoaming agent, and 1-3 parts of stabilizer. The composite glue is mixed with DY5010 latex powder, ethylene/vinyl acetate copolymer powder and silane coupling agent, and obtained by insulating and activation treatment at 60-70°C in water bath; the stabilizer is composed of a mixture of zinc stearate and ethylene bisstearic acid amide.

Benefits of technology

This scale inhibitor has good scale inhibition properties for CaCO3, CaSO4, and SiO2, expands the scope of application of scale inhibitors, improves scale inhibition effect, reduces the use of a single scale inhibitor, thereby reducing costs, and ensuring the long-term stable and efficient operation of the water treatment system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005199323350000041
    Figure BDA0005199323350000041
  • Figure BDA0005199323350000061
    Figure BDA0005199323350000061
  • Figure BDA0005199323350000071
    Figure BDA0005199323350000071
Patent Text Reader

Abstract

The invention relates to the technical field of scale inhibitors and particularly discloses a scale inhibitor for ultrafiltration and reverse osmosis processes as well as a preparation method and application of the scale inhibitor. The scale inhibitor disclosed by the invention is specifically prepared from the following components in parts by weight: 20 to 30 parts of polyaspartic acid, 5 to 9 parts of polyepoxysuccinic acid, 5 to 9 parts of a composite sizing material, 1 to 3 parts of a de-foaming agent and 1 to 3 parts of a stabilizer, the composite sizing material is obtained by activating a mixture of DY5010 latex powder, ethylene / vinyl acetate copolymerized rubber powder and a silane coupling agent in a water bath at the temperature of 60-70 DEG C for 3-5 hours; the stabilizer is formed by mixing zinc stearate and ethylene bis stearamide according to the weight ratio of 9: (0.5-5). The scale inhibitor prepared by using the technical scheme provided by the invention has excellent scale inhibition performance, and is wide in scale inhibition spectrum and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of scale inhibitors, and in particular to a scale inhibitor used in ultrafiltration and reverse osmosis processes, and a preparation method and application thereof. Background Art

[0002] During the ultrafiltration and reverse osmosis process, calcium, magnesium, iron and other ions in the water may form a scale layer, which will not only affect the permeability of the membrane, reduce the water production efficiency, but also may damage the membrane components. Therefore, in order to prevent the ultrafiltration and reverse osmosis membranes from being blocked by scales enriched by salt in the water, it is generally necessary to add an appropriate amount of scale inhibitor at the water inlet of the system to protect the membrane.

[0003] At present, there are many types of scale inhibitors on the market, such as organic scale inhibitors, inorganic scale inhibitors and composite scale inhibitors. With the advancement of science and technology and the improvement of environmental protection requirements, the research and development and application of new green scale inhibitors have become a hot topic. For example, the development of phosphorus-free or low-phosphorus scale inhibitors to reduce the risk of eutrophication of water bodies, and the use of biodegradable materials to reduce the impact on the environment. However, these new materials still face many challenges in practical applications, such as the complexity of production processes, cost issues, and long-term effect verification. In actual industrial applications, how to ensure the long-term stability and broad-spectrum scale inhibition of scale inhibitors is one of the problems that need to be solved in the research and development of scale inhibitor materials. Summary of the invention

[0004] In order to solve the above technical problems, the present application provides a scale inhibitor for use in ultrafiltration and reverse osmosis processes, and a preparation method and application thereof.

[0005] The present application provides a scale inhibitor for use in ultrafiltration and reverse osmosis processes, specifically comprising the following components in parts by weight: 20-30 parts of polyaspartic acid, 5-9 parts of polyepoxysuccinic acid, 5-9 parts of composite rubber, 1-3 parts of defoaming agent, and 1-3 parts of stabilizer; The composite rubber material is obtained by treating a mixture of DY5010 latex powder, ethylene / vinyl acetate copolymer rubber powder and a silane coupling agent in a water bath at 60-70° C. for 3-5 hours. The stabilizer is composed of a mixture of zinc stearate and ethylene bis stearamide in a weight ratio of 9:0.5-5.

[0006] The scale inhibitor prepared in the present application by utilizing the above technical solution has good scale inhibition performance for CaCO3, CaSO4, and SiO2, thus expanding the application scope of the scale inhibitor.

[0007] Functional groups such as carboxyl and amino groups in the PASP polyaspartic acid (PASP) molecule can undergo chelation reactions with metal ions such as calcium and magnesium in water to form stable soluble complexes, thereby preventing these ions from combining with anions such as carbonate to form insoluble scale. PASP also has good dispersibility and can disperse the already formed tiny scale particles in the water to prevent them from depositing and aggregating into large scale.

[0008] Polyepoxysuccinic acid (PESA) can be adsorbed on the metal surface to form a protective film to prevent scale-forming ions in the water from depositing on the metal surface; at the same time, it can also combine with calcium, magnesium and other ions in the water to form a water-soluble complex, thereby preventing the formation of scale. Polyepoxysuccinic acid is a green and environmentally friendly scale inhibitor that is biodegradable and harmless to the environment.

[0009] The components in the composite rubber can work synergistically to form a protective film, which effectively prevents metal ions such as calcium and magnesium in the water from combining with anions such as carbonate, thereby preventing the formation of scale; at the same time, it can also keep the tiny scale particles that have been formed in a suspended state to prevent them from settling and aggregating. Through a specific water bath insulation activation treatment, the stability and dispersibility of the composite rubber are improved. This enables it to be better evenly distributed in the water, exert its scale inhibition effect, and at the same time extend its service life. The composite rubber provided in this application has thickening and suspension functions, which can effectively increase the viscosity of the water body, so that the tiny scale particles remain suspended in the water and are not easy to deposit. When used in combination with polyaspartic acid and polyepoxysuccinic acid scale inhibitors, the composite rubber can play a synergistic role and enhance the overall scale inhibition effect.

[0010] The zinc stearate and ethylene bis stearamide components in the stabilizer can interact with each other to form a protective film, which effectively prevents scale-forming ions (such as calcium and magnesium ions) in the water from combining to form scale. At the same time, it can also keep the already formed tiny scale particles in a dispersed state to prevent them from depositing on the surface of equipment or pipes. The mixture of zinc stearate and ethylene bis stearamide has good stability and can maintain its scale inhibition effect under different water quality conditions; so that the scale inhibitor can effectively play a role in various environments and reduce the formation of scale. After the two components are mixed, they may produce a synergistic effect and enhance each other's scale inhibition effect. This synergistic effect may come from the chemical reaction or physical interaction between them, thereby improving the overall scale inhibition efficiency.

[0011] In summary, in order to further improve the scale inhibition effect, the scale inhibitor provided by this application can give full play to the advantages of various scale inhibitors through the combined action of multiple mechanisms such as chelation, dispersion, adsorption and thickening, effectively prevent and reduce the formation and deposition of scale, and achieve a better synergistic scale inhibition effect. It has good and sufficient effects on a variety of substances and has a wide range of applications; it not only improves the scale inhibition performance, but also reduces the use of a single scale inhibitor, thereby reducing costs. This is of great significance for keeping the water treatment system clean and running efficiently.

[0012] Preferably, the scale inhibitor specifically comprises the following components in parts by weight: 23-28 parts of polyepoxysuccinic acid, 10-13 parts of polyaspartic acid, 6-8 parts of composite rubber, 1.5-2.5 parts of defoaming agent, and 1.5-2.5 parts of stabilizer.

[0013] Preferably, the scale inhibitor specifically comprises the following components in parts by weight: 25 parts of polyepoxysuccinic acid, 12 parts of polyaspartic acid, 7 parts of composite rubber, 2 parts of defoamer, and 2 parts of stabilizer.

[0014] Preferably, the composite rubber material is obtained by treating a mixture of DY5010 latex powder, ethylene / vinyl acetate copolymer rubber powder and silane coupling agent in a weight ratio of 5-15:5-15:1-3, and activating the mixture in a water bath at 60-70°C for 3-5 hours.

[0015] Preferably, the composite rubber material is obtained by treating a mixture of DY5010 latex powder, ethylene / vinyl acetate copolymer rubber powder and silane coupling agent in a weight ratio of 10-15:5-10:1-3, and activating the mixture in a water bath at 60-70°C for 3-5 hours.

[0016] Preferably, the stabilizer is composed of a mixture of zinc stearate and ethylene bisstearamide in a weight ratio of 9:1-3.

[0017] In some specific embodiments, in the stabilizer, the weight ratio of zinc stearate to ethylene bisstearamide is 9:0.5-1, 9:0.5-2, 9:0.5-3, 9:0.5-4, 9:0.5-5, 9:2-3, 9:2-4, 9:2-5, 9:3-4, 9:3-5, 9:4-5.

[0018] In a specific embodiment, in the stabilizer, the weight ratio of zinc stearate to ethylene bisstearamide can also be 9:0.5, 9:1, 9:2, 9:3, 9:4, or 9:5.

[0019] Through experimental analysis, it can be known that the present application further improves the performance of the scale inhibitor by controlling the weight ratio of zinc stearate and ethylene bisstearamide within the above range.

[0020] Preferably, the defoaming agent is selected from one or more of polydimethylsiloxane and polysiloxane polyether.

[0021] Preferably, in the preparation method of the composite rubber material, the silane coupling agent is selected from one or more of vinyl triethoxysilane, aminopropyl triethoxysilane, vinyl trimethoxysilane, vinyl tri(β-methoxyethoxy)silane, methacryloxypropyl trimethoxysilane, glycidyl methoxypropyl trimethoxysilane, ethylenediaminepropyl triethoxysilane, vinyl triethoxysilane, mercaptopropyl trimethoxy(ethyl)silane, and ethylenediaminepropyl methyldimethoxysilane.

[0022] In a second aspect, the present application provides a method for preparing the above-mentioned scale inhibitor, which specifically comprises the following steps in sequence: Weigh the corresponding weight of each raw material component respectively, put each raw material and water in a stirring kettle, stir for 40-90 minutes, and let it stand for 10-15 minutes to obtain the product.

[0023] In a third aspect, the present application provides the use of the above-mentioned scale inhibitor in wastewater treatment.

[0024] In summary, the technical solution of this application has the following effects: The present application utilizes a mixture of DY5010 latex powder, ethylene / vinyl acetate copolymer rubber powder and silane coupling agent, and obtains a composite rubber material by heat-insulating and activating it in a water bath at 60-70°C for 3-5h. A stabilizer is formed by mixing zinc stearate and ethylene bisstearamide in a weight ratio of 9:0.5-5, and a specific amount of polyaspartic acid, polyepoxysuccinic acid and a defoaming agent are used as raw materials. The prepared scale inhibitor has good scale inhibition performance for CaCO3, CaSO4 and SiO2, thereby expanding the scope of application of the scale inhibitor.

[0025] The present application optimizes the preparation method of the composite rubber and the type of stabilizer, brings into play the matching effect of each raw material, and further improves the performance of the scale inhibitor. DETAILED DESCRIPTION

[0026] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application.

[0027] DY5010 latex powder and DY5020 latex powder were purchased from Guangzhou Yuanye Industrial Co., Ltd.; ethylene / vinyl acetate copolymer rubber powder and versatate / vinyl acetate / ethylene homopolymer rubber powder were purchased from Guangzhou Yuanye Industrial Co., Ltd.; titanate coupling agent was purchased from Henan Jiyuan Kehui Materials Co., Ltd., and the remaining raw materials were commercially available. Example

[0028] Examples 1-5 Examples 1-5 respectively provide a scale inhibitor and a preparation method thereof.

[0029] The difference between the above embodiments is that the dosage of each component in the scale inhibitor is different, as shown in Table 1.

[0030] The preparation method of the scale inhibitor in the above embodiment is: Preparation of composite rubber: According to the weight ratio of 12:7:2, 12g of DY5010 latex powder, 7g of ethylene / vinyl acetate copolymer powder and 2g of methacryloxypropyltrimethoxysilane were weighed respectively and the mixture was activated at 65°C in a water bath for 4h.

[0031] According to Table 1, weigh the corresponding weights of each raw material component of polyepoxysuccinic acid, polyaspartic acid, composite rubber, defoamer, and stabilizer (composed of a mixture of zinc stearate and ethylene bisstearamide in a weight ratio of 9:2), put each raw material and water in a stirring kettle, start the stirring rod at a speed of 800 rpm, stir for about 60 minutes, and let it stand for 12 minutes to obtain the product.

[0032] Table 1 Amount of each component in the scale inhibitor in Examples 1-5 and Comparative Examples 1-3 Examples 6-10 Examples 6-10 respectively provide a scale inhibitor and a preparation method thereof.

[0033] The difference between the above embodiment and embodiment 2 is that the preparation method of the composite rubber material is different, as shown below.

[0034] In Example 6: Preparation of composite rubber: According to the weight ratio of 1:7:2, a mixture of 12g of DY5010 latex powder, 7g of ethylene / vinyl acetate copolymer powder and 2g of silane coupling agent was weighed and activated in a water bath at 85°C for 4h.

[0035] In Example 7: Preparation of composite rubber: According to the weight ratio of 7:12:2, a mixture of 12g DY5010 latex powder, 7g ethylene / vinyl acetate copolymer powder and 2g silane coupling agent was weighed and activated in a water bath at 65°C for 4h.

[0036] In Example 8: Preparation of composite rubber: According to the weight ratio of 5:15:2, a mixture of 12g of DY5010 latex powder, 7g of ethylene / vinyl acetate copolymer powder and 2g of silane coupling agent was weighed and activated in a water bath at 65°C for 4h.

[0037] In Example 9: Preparation of composite rubber: According to the weight ratio of 10:10:2, a mixture of 12g of DY5010 latex powder, 7g of ethylene / vinyl acetate copolymer powder and 2g of silane coupling agent was weighed and activated in a water bath at 65°C for 4h.

[0038] In Example 10: Preparation of composite rubber: According to the weight ratio of 15:5:2, a mixture of 12g of DY5010 latex powder, 7g of ethylene / vinyl acetate copolymer powder and 2g of silane coupling agent was weighed and activated in a water bath at 65°C for 4h.

[0039] The other process parameters in the above embodiment are the same as those in embodiment 2.

[0040] Examples 11-14 Examples 11-14 respectively provide a scale inhibitor and a preparation method thereof.

[0041] The difference between the above embodiment and embodiment 2 is that the types of stabilizers are different, as shown below.

[0042] In Example 11: the stabilizer is composed of a mixture of zinc stearate and ethylene bisstearamide in a weight ratio of 9:0.5.

[0043] In Example 12: the stabilizer is composed of a mixture of zinc stearate and ethylene bisstearamide in a weight ratio of 9:5.

[0044] In Example 13: the stabilizer is composed of a mixture of zinc stearate and ethylene bisstearamide in a weight ratio of 9:1.

[0045] In Example 14: the stabilizer is composed of a mixture of zinc stearate and ethylene bisstearamide in a weight ratio of 9:3.

[0046] The other process parameters in the above embodiment are the same as those in embodiment 2.

[0047] Comparative Example Comparative Examples 1-3 Comparative Examples 1-3 respectively provide a scale inhibitor and a preparation method thereof.

[0048] The difference between the comparative example and Example 2 is that the dosage of each component in the scale inhibitor is different, as shown in Table 1.

[0049] The other process parameters in the above comparative example are the same as those in Example 2.

[0050] Comparative Examples 4-7 Comparative Examples 4-7 respectively provide a scale inhibitor and a preparation method thereof.

[0051] The differences between the above comparative example and Example 2 are specifically as follows.

[0052] In comparative example 4: Preparation of composite rubber: According to the weight ratio of 12:7:2, a mixture of 12g of DY5020 latex powder, 7g of versatate / vinyl acetate / ethylene copolymer rubber powder and 2g of silane coupling agent was weighed and activated in a water bath at 65°C for 4h.

[0053] In Comparative Example 5: Preparation of composite rubber: 19 g of DY5020 latex powder and 2 g of silane coupling agent were weighed respectively and the mixture was activated by heat preservation at 65° C. in a water bath for 4 h.

[0054] In Comparative Example 6: the stabilizer is composed of a mixture of zinc stearate and polyethylene wax in a weight ratio of 9:2.

[0055] In Comparative Example 7: the stabilizer is zinc stearate.

[0056] The other process parameters in the above comparative example are the same as those in Example 2.

[0057] Performance testing (1) Scale inhibition rate test: According to GB / T 16632-2008 "Determination of scale inhibition performance of water treatment agents - Calcium carbonate deposition method", the scale inhibition rate of CaCO3 is determined by using deionized water to prepare CaCO3. 2+ The mass concentration is 260mg / L, HCO3 - The solution with a mass concentration of 760 mg / L was adjusted to pH 9.0 with sodium hydroxide, then placed in a constant temperature water bath at 60°C for 10 hours, cooled, filtered with a 0.22 μm microporous filter, and the Ca content was determined by the EDTA method. 2+ concentration and perform a blank test at the same time.

[0058] CaSO4 scale inhibition performance test was carried out according to the standard QSY126-2014 "Requirements for Corrosion and Scale Inhibitors for Oilfield Water Treatment": CaSO4 was prepared with deionized water. 2+ The mass concentration is 260mg / L, SO4 2- The solution with a mass concentration of 760 mg / L was adjusted to pH 9.0 with sodium hydroxide, then placed in a constant temperature water bath at 60°C for 10 hours, cooled, filtered with a 0.22 μm microporous filter, and the Ca content was determined by the EDTA method. 2+ concentration and perform a blank test at the same time.

[0059] The anti-scaling performance of silica scale inhibitors was determined according to the standard GB / T 16633-1996 "Determination of silicon dioxide content in industrial circulating cooling water - spectrophotometric method", that is, the silicon molybdenum blue spectrophotometric method: a Na2SiO3 solution with a mass concentration of 500 mg / L (concentration in terms of SiO2) was prepared with deionized water, 50 mg / L of scale inhibitor was added, the pH value of the solution was adjusted to 7.0, and then placed in a constant temperature water bath at 40°C for 8 hours, cooled, filtered with a 0.22μm microporous filter, and the SiO2 content in the water sample was determined by silicon molybdenum blue spectrophotometry, and a blank test was performed at the same time.

[0060] Test results: as shown in Table 2.

[0061] Table 2 Performance test results of scale inhibitors in Examples 1-14 and Comparative Examples 1-7 Combined with the test results of Table 2, by comparing the test results of the embodiment and the comparative example, it can be known that the present application utilizes a mixture of DY5010 latex powder, ethylene / vinyl acetate copolymer rubber powder and a silane coupling agent, which is treated by heat preservation and activation at 60-70°C in a water bath for 3-5h to obtain a composite rubber material, and a stabilizer is composed of a mixture of zinc stearate and ethylene bisstearamide in a weight ratio of 9:0.5-5, and a specific amount of polyaspartic acid, polyepoxysuccinic acid, and a defoaming agent are used as raw materials. The prepared scale inhibitor has good scale inhibition performance for CaCO3, CaSO4, and SiO2, thereby expanding the scope of application of the scale inhibitor.

[0062] No composite rubber was added in Comparative Example 1, no stabilizer was added in Comparative Example 2, the amounts of the raw material components in Comparative Example 3 were not matched, the preparation methods of the composite rubbers in Comparative Examples 4-5 were not matched, the stabilizer in Comparative Example 6 was a mixture of zinc stearate and polyethylene wax in a weight ratio of 9:2, and the stabilizer in Comparative Example 7 was zinc stearate. The performance of the scale inhibitors prepared in the above comparative examples was poor.

[0063] By comparing the test results of Examples 2 and 6-10, it can be seen that the present application further improves the performance of the scale inhibitor by treating a mixture of DY5010 latex powder, ethylene / vinyl acetate copolymer powder and silane coupling agent in a weight ratio of 5-15:5-15:1-3 and activating it in a water bath at 60-70°C for 3-5h to obtain a composite rubber material.

[0064] By comparing the test results of Examples 2 and 11-14, it can be seen that the present application further improves the performance of the scale inhibitor by mixing zinc stearate and ethylene bisstearamide in a weight ratio of 9:1-3 to form a stabilizer.

[0065] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A scale inhibitor for ultrafiltration and reverse osmosis processes, characterized in that: Specifically, it includes the following components in parts by weight: 20-30 parts of polyaspartic acid, 5-9 parts of polyepoxysuccinic acid, 5-9 parts of composite rubber, 1-3 parts of defoaming agent, and 1-3 parts of stabilizer; The composite rubber material is obtained by treating a mixture of DY5010 latex powder, ethylene / vinyl acetate copolymer rubber powder and a silane coupling agent in a water bath at 60-70° C. for 3-5 hours. The stabilizer is composed of a mixture of zinc stearate and ethylene bis stearic acid amide in a weight ratio of 9:0.5-5.

2. The scale inhibitor according to claim 1, characterized in that The scale inhibitor specifically comprises the following components in parts by weight: 23-28 parts of polyepoxysuccinic acid, 10-13 parts of polyaspartic acid, 6-8 parts of composite rubber, 1.5-2.5 parts of defoaming agent, and 1.5-2.5 parts of stabilizer.

3. The scale inhibitor according to claim 1, characterized in that: The scale inhibitor specifically comprises the following components in parts by weight: 25 parts of polyepoxysuccinic acid, 12 parts of polyaspartic acid, 7 parts of composite rubber, 2 parts of defoaming agent, and 2 parts of stabilizer.

4. The scale inhibitor according to claim 3, characterized in that: The composite rubber material is obtained by treating a mixture of DY5010 latex powder, ethylene / vinyl acetate copolymer rubber powder and silane coupling agent in a weight ratio of 5-15:5-15:1-3, and activating the mixture in a water bath at 60-70°C for 3-5 hours.

5. The scale inhibitor according to claim 1, characterized in that: The composite rubber material is obtained by treating a mixture of DY5010 latex powder, ethylene / vinyl acetate copolymer rubber powder and silane coupling agent in a weight ratio of 10-15:5-10:1-3, and activating the mixture in a water bath at 60-70°C for 3-5 hours.

6. The scale inhibitor according to claim 1, characterized in that: The stabilizer is composed of a mixture of zinc stearate and ethylene bis stearamide in a weight ratio of 9:1-3.

7. The scale inhibitor according to claim 6, characterized in that: The defoaming agent is selected from one or more of polydimethylsiloxane and polysiloxane polyether.

8. The scale inhibitor according to claim 1, characterized in that: In the preparation method of the composite rubber material, the silane coupling agent is selected from one or more of vinyl triethoxysilane, aminopropyl triethoxysilane, vinyl trimethoxysilane, vinyl tri(β-methoxyethoxy)silane, methacryloxypropyl trimethoxysilane, glycidyl methoxypropyl trimethoxysilane, ethylenediamine propyl triethoxysilane, vinyl triethoxysilane, mercaptopropyl trimethoxy(ethyl)silane, and ethylenediamine propyl methyl dimethoxysilane.

9. The method for preparing the scale inhibitor according to any one of claims 1 to 8, characterized in that: Specifically, the following steps are performed in sequence: Weigh the corresponding weight of each raw material component respectively, put each raw material and water in a stirring kettle, stir for 40-90 minutes, and let it stand for 10-15 minutes to obtain the product.

10. Use of the scale inhibitor according to any one of claims 1 to 8 in wastewater treatment.

Citation Information

Patent Citations

  • Antisludging agent for osmosis-reverse membrane and method of preparing the same

    CN101138705A

  • Composite scale inhibitor for circulating cooling water and preparation method thereof

    CN109835989A

  • Polyester elastomer as well as preparation method and application thereof

    CN118360686A

  • Scale and corrosion inhibition composition as well as preparation method and water treatment application thereof

    CN118724302A